Epigenetic regulation of MicroRNA‐122 by peroxisome proliferator activated receptor‐gamma and hepatitis b virus X protein in hepatocellular carcinoma cells. Issue 5 (17th September 2013) - Song, Kyoungsub; Han, Chang; Zhang, Jinqiang; Lu, Dongdong; Dash, Srikanta; Feitelson, Mark; Lim, Kyu; Wu, Tong
Abstract : MicroRNA‐122 (miR‐122), a pivotal liver‐specific miRNA, has been implicated in several liver diseases including hepatocellular carcinoma (HCC) and hepatitis C and B viral infection. This study aimed to explore epigenetic regulation of miR‐122 in human HCC cells and to examine the effect of hepatitis C virus (HCV) and hepatitis B virus (HBV). We performed microRNA microarray analysis and identified miR‐122 as the most up‐regulated miRNA (6‐fold) in human HCC cells treated with 5′aza‐2′deoxycytidine (5‐Aza‐CdR, DNA methylation inhibitor) and 4‐phenylbutyric acid (PBA, histone deacetylation inhibitor). Real‐time polymerase chain reaction (PCR) analysis verified significant up‐regulation of miR‐122 by 5′aza and PBA in HCC cells, and to a lesser extent in primary hepatocytes. Peroxisome proliferator activated receptor‐gamma (PPARγ) and retinoid X receptor alpha (RXRα) complex was found to be associated with the DR1 and DR2 consensus site in the miR‐122 gene promoter which enhanced miR‐122 gene transcription. 5‐Aza‐CdR and PBA treatment increased the association of PPARγ/RXRα, but decreased the association of its corepressors (N‐CoR and SMRT), with the miR‐122 DR1 and DR2 motifs. The aforementioned DNA‐protein complex also contains SUV39H1, an H3K9 histone methyl transferase, which down‐regulates miR‐122 expression. Conclusions : These findings establish a novel role of the PPARγ binding complex for epigenetic regulation of miR‐122 in human HCC cells. Moreover, we show that hepatitis B virus X protein binds PPARγ and inhibits the transcription of miR‐122, whereas hepatitis C viral particles exhibited no significant effect; these findings provide mechanistic insight into reduction of miR‐122 in patients with HBV but not with HCV infection. (Hepatology 2013;58:1681–1692)